Judge not? The pedagogical puzzle of right interpretation and wrong interpretation - Esterson, Rebecca K. (2021)
When studying the reception history of the Bible, should students be asked to suspend judgment on a particular interpretation for the sake of the pedagogical goals of the course? Or is their judgment essential to the process of learning and understanding? This essay explores the pedagogical puzzle of right interpretation and wrong interpretation through the context of my classroom, where neither the troubling events of a nation in turmoil nor our own social, religious, and cultural locations as readers could be bracketed from the learning environment, despite my best efforts. In particular, this essay integrates the approach outlined by Gary Weissman, who argues for an embrace of student misreading in his book The Writer in the Well. His suggestion that misreading and rewriting are fundamental to the process of understanding is provocative, and its application to biblical studies presents special challenges, but this paper argues for its relevance to the pedagogical puzzle at hand.
Keywords: Biblical Interpretation; Judgment; misreading; Pedagogy; Reception History; Writing